Evaluation of Calcein and Photonic Marking for Cultured Delta Smelt. (14th January 2014) - Castillo, Gonzalo; Morinaka, Jerry; Fujimura, Robert; DuBois, Jason; Baskerville‐Bridges, Bradd; Lindberg, Joan; Tigan, Galen; Ellison, Luke; Hobbs, James
Abstract: The Delta Smelt Hypomesus transpacificus is a protected osmerid endemic to the San Francisco estuary of California. We conducted laboratory tests on marked versus unmarked juvenile adult smelt to evaluate (1) calcein mark intensity and postmarking survival for juveniles and adults, (2) photonic mark retention and survival of adults, and (3) predation by juvenile Striped Bass Morone saxatilis . Calcein mark intensity was graded in six body sections and adults were photonically marked using four fin‐color combinations. Across all immersion times (1–7 min) all fish showed 100% mark retention 7 d after exposure to calcein concentrations of 2.5 and 5.0 g/L of water. Average survival 7 d after calcein marking was 93.9% in juveniles and 98.6% in adults. After 97 d of calcein and photonic marking, adults had weaker double marking, but each type of mark still showed 100% retention. Average survival of adult fish 70 d after marking was 98.7%. Unmarked and calcein + photonically marked adult Delta Smelt exposed to juvenile Striped Bass did not experience significantly different predation rates. Calcein is both effective and practical to batch‐mark juvenile and adult Delta Smelt. Combined calcein and photonic marking for adult Delta Smelt further enables identification of multiple groups while potentially improving mark detection in short‐term studies. Received October 1, 2012; accepted August 22, 2013 Published online January 14, 2014